Entrepreneurship as part of career, yay or nay? - Mohamad, Zuraida; Mhd Atan, Ira Mazliana; Abd Ghani, Roseziahazni; Abu Samah, A’tiqah Rashidah; Yusof Ali, Noorhayati (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2023)
Entrepreneurship is the process of developing, organizing, and managing a new business idea in a dynamic global marketplace. The modern entrepreneurship definition is about transforming the world by solving big problems like bringing about social change or creating an innovative product that challenges the status quo of how we live our lives daily. Entrepreneurs play a key role in any economy. These are the people who have the skills and initiative necessary to take new ideas in marketing their product and make the right decisions to ensure the ideas are profitable.